The effectiveness of bio-melioration technologies in restoring and improving the fertility of degraded soils - Panasiuk, O.; Kostiuk, V. (Land Management, Cadastre and Land Monitoring, 2025)
The article addresses the pressing issue of soil degradation and substantiates the necessity of applying biomelioration methods as a key tool for restoring soil fertility. The purpose of the study is to analyze and systematize data on the impact of biomelioration techniques based on fertility indicators of degraded soils. A comprehensive research approach was employed, which included the analysis of scientific publications as well as practical examples of biomelioration methods used to improve the fertility of degraded soils. Fertility is defined as a combination of three main properties: physical, chemical, and biological. The study highlights the influence of biomelioration methods on fertility restoration through the accumulation of organic matter, stimulation of biological activity, and improvement of soil structure. The main biomelioration techniques and their effects have been examined. Phytoremediation is considered as a measure aimed at reducing toxic elements in contaminated soils by cultivating special plants capable of removing or localizing toxic substances within the root zone or aerial parts. The role of organic farming as a biomelioration method has been determined. A schematic model illustrating the mechanism of biomelioration effects on soil fertility is presented, along with recommendations for implementing a complex system of biomelioration practices to effectively restore degraded soils in Ukraine. It is noted that further research should focus on the development of regionally adapted biomelioration systems and the assessment of the long-term economic impact of their implementation.Keywords: soil degradation, soil fertility, biomelioration, green manures, phytomelioration, phytoremediation, microbial preparations, organic farming.
Keywords: soil degradation; soil fertility; biomelioration; green manures; phytomelioration; phytoremediation; microbial preparations; organic farming